PENGEMBANGAN MODEL REFLEKSI PADA LESSON STUDY UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN IPA DI SEKOLAH - Laelawati, Susi (2016)
Penelitian ini merupakan penelitian dan pengembangan yang bertujuan untuk mengembangkan model refleksi pada lesson study dalam meningkatkan kualitas pembelajaran IPA di sekolah. Tahapan pengembangan meliputi studi pendahuluan, perencanaan, pengembangan, validasi dan revisi. Uji coba dilakukan enam kali di dua sekolah dengan melibatkan dua orang guru model dan sepuluh guru observer. Berdasarkan hasil studi pendahuluan diperoleh temuan bahwa refleksi selama ini belum terdokumentasikan, masih memberi tanggapan negatif terhadap guru model dan hasil refleksi belum mengarah pada peningkatan kualitas pembelajaran. Berdasarkan hasil studi pendahuluan tersebut maka dipandang perlu untuk mengembangkan model refleksi. Pengembangan model refleksi difokuskan pada adanya lembar self reflection untuk guru model dan lembar other reflection untuk observer sebagai perbedaan dengan kegiatan refleksi sebelumnya. Kualitas refleksi yang mengarah pada peningkatan kualitas pembelajaran diperoleh dari hasil analisis data yang dikumpulkan setelah proses refleksi selesai. Data-data meliputi: hasil lembar self reflection dan hasil lembar other reflection serta hasil field notes. Hasil lembar self reflection menunjukkan bahwa guru model merasa lebih mudah mengemukakan temuannya serta lebih percaya diri dan nyaman. Hasil lembar other reflection memudahkan observer dalam mengamati aktivitas siswa serta lebih fokus dalam mengemukakan temuannya. Hasil implementasi model refleksi menunjukkan 1) kegiatan refleksi fokus pada aktivitas belajar siswa, 2) observer mengambil pelajaran positif dari guru model, 3) refleksi meningkatkan kualitas pembelajaran IPA. Produk pengembangan model refleksi dituangkan dalam bentuk buku panduan lessson study berbasis model refleksi SELFOR.;--- This research aims to develop a model of reflection on lesson study to improve the quality of learning and science in school. The method of this research is research and development.. Stages of development include preliminary studies, planning, development, validation and revision. The real test is performed before the development of a model of reflection and trial was conducted six times in two schools with involved two teachers as model and ten teachers as observer. Based on the preliminary results obtained findings that have not been documented for this reflection, still give negative feedback on the results of the reflection model and the teachers have not yet led to an increase in the quality of learning. Based on results of those primaries were seen to need to develop a model of reflection. The reflection model developed using the instrument self reflection sheets and other reflection sheets. The results of the tests, earned that instrument, namely sheets of self reflection and other pieces of reflection makes it easy for teachers to do reflection. To see the quality of the reflection which can lead to increased quality of learning conducted an analysis of the data is already collected by way of grouping categories that appear at the moment of reflection, the pattern tendency of results of self reflection and other reflection. The results of self reflection that is created to facilitate teachers to state its findings on learning can be read well and makes it easy for the teacher models, more confident and comfortable. The results of the test sheet other reflection shows that there is a tendency for the observer to observe the learning process in the classroom as a reflection. The implementation results show the reflection model 1) the reflection focus on student learning activities, 2) observer take positive lessons from the teacher models, 3) reflection of improving the quality of science teaching. Product of development reflection model is guide books lessson study based SELFOR reflection model.